2008
DOI: 10.1590/s0004-282x2008000200013
|View full text |Cite
|
Sign up to set email alerts
|

Stroke awareness among cardiovascular disease patients

Abstract: -Background: The early recognition of stroke signs and symptoms is of great relevance concerning the outcome, since it enhances the chances of thrombolytic therapy use. Purpose: To compare the knowledge of stroke among a community-based sample and patients treated in a cardiologic clinic. Method: We applied a questionnaire during one morning to people who were walking in a park (Pa) and spontaneously stopped at a health tent and during one week to patients of a cardiologic clinic (Ca). The survey assessed demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
4
0
3
Order By: Relevance
“…Perhaps this might also be related to personal health problems. However, it has been shown that awareness about stroke risk factors and symptoms among the cardiovascular patients is about the same as among the ordinary population [18] and plausibly this shortage did not significantly influence our results. Secondly, it should be noted that we used a closed-ended questionnaire where the respondents had to choose correct answers.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Perhaps this might also be related to personal health problems. However, it has been shown that awareness about stroke risk factors and symptoms among the cardiovascular patients is about the same as among the ordinary population [18] and plausibly this shortage did not significantly influence our results. Secondly, it should be noted that we used a closed-ended questionnaire where the respondents had to choose correct answers.…”
Section: Discussionmentioning
confidence: 64%
“…Numerous studies using different methods (telephone interviews, face-to-face questioning, internet-based surveys, etc.) have confirmed low public awareness of stroke warning signs and stroke risk factors which contribute to late arrival and limited use of thrombolysis [9,13,14,15,16,17,18,19,20,21]. A recent study of risk factor awareness among stroke survivors showed that older patients and those with excellent recovery are at risk for poor awareness even after stroke [22].…”
Section: Introductionmentioning
confidence: 99%
“…The number needed to treat in these studies ranged from 3 to 5 ( Figure). Despite several published studies having shown that much of the population cannot identify the symptoms of stroke, resulting in a delay reaching the hospital 4,5,6,7,8 , we aimed to quantify the current knowledge of physicians regarding the 'state-of-the-art' treatment for acute stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Já os fatores de risco não modificáveis são idade, gênero e raça 3,6 . A estratégia terapêutica mais eficaz para o AVC isquêmico é a administração de Alteplase IV, porém ela só pode ser realizada em até 4,5 h após o início dos sintomas, fato que evidencia a importância de reconhecer rapidamente o quadro 7,8 .…”
Section: Introductionunclassified
“…Acredita-se que uma maior conscientização da população sobre a gravidade do AVC e a identificação de seus sinais e sintomas podem aumentar as chances do paciente de receber o tratamento ideal e ter uma evolução satisfatória, já que esta patologia é uma das principais causas de incapacidade permanente e a principal causa de morte no Brasil 1,2,7 . Pesquisas em geral mostram que, apesar de campanhas de conscientização, existe alto índice de desconhecimento da população frente aos primeiros sinais e sintomas do AVC 9 .…”
Section: Introductionunclassified